The relationship between critical thinking disposition, attitude and perception of special education teachers in cooperative teaching with mind map - Kuppusamy, Suresh Kumar; Sulaiman, Tajularipin; Abdul Manaf, Umi Kalthom (International Journal of Current Research, 2016)
This study aims to assess the level of critical thinking dispositions, attitudes and perceptions in cooperative teaching with mind map among teachers in Negeri Sembilan. This study also examined the relationship between critical thinking disposition, attitude and perception of Special Education teacher in cooperative teaching with mind map. Critical thinking disposition has seven subscales measured by curiosity, open-minded, systematic, accuracy, truth-seeking, self-confidence and maturity. Special education teacher attitudes in cooperative teaching with mind map has three subscales namely cognitive, affective and behavioural. Special Education teachers in cooperative teaching with mind map has three subscales which are interpersonal relationships, motivation, support and guidance in their studies lessons. A total of 190 primary school of Special Education teachers in Negeri Sembilan have been selected using proportional sampling method. The instrument is based on previous research instrument and modifications made to the item so that it's relevant to the current study. Raw data obtained were analysed using SPSS. The descriptive analysis showed that the respondents have a level of critical thinking dispositions (M = 2.99, SD = 0.160), attitude in cooperative teaching with mind map (M = 2.96, SD = 0.194) and the perception of the cooperative teaching with mind map (M = 3.00, SD = 0.240) were moderate. The inference analysis showed novice teachers have a significantly higher critical thinking dispositions and attitudes of cooperative teaching with mind map compared with experienced teachers. For the gender, no significant differences between male and female teachers to construct critical thinking dispositions, attitudes and perceptions of cooperative teaching with mind map. The findings shows there is a significant positive relationship between critical thinking disposition and attitude (r = .443, p <.01) and perception (r = .442, p <.01) among Special Education teacher. This study suggested that the critical thinking disposition of teachers should be given special attention in order to improve the effectiveness of teaching to their Special Education student. Special Education teachers should also be exposed to the latest teaching methods so that student achievement can be improved.